2019
DOI: 10.21203/rs.2.16736/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term Outcomes of Robotic- versus Laparoscopic-Assisted Total Gastrectomy for Advanced Gastric Cancer: A Propensity Score Matching Study

Abstract: Background Few studies have been designed to evaluate the short-term outcomes for advanced gastric cancer (AGC) between robotic-assisted total gastrectomy (RATG) and laparoscopy-assisted total gastrectomy (LATG) alone. The purpose of this study was to assess short-term outcomes of RATG compared with LATG for AGC.Methods We retrospectively evaluated 116 and 244 patients who underwent RATG or LATG respectively. Besides, we performed a propensity score matching (PSM) analysis between RATG and LATG for clinicopath… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This finding could be attributed to the advanced robotic surgery systems, including an internal EndoWrist with seven degrees of freedom, three-dimensional vision, tremor filter, and short learning curve, which prevented injuries from the blood vessels and allowed precise dissection and high flexibility for surgeons [32]. Previous studies proved that one critical barrier to the wide RG application in clinical practice was high costs [12,13,16,17,33,34]. Our study also found that RADG group had higher medical cost than the LADG group.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…This finding could be attributed to the advanced robotic surgery systems, including an internal EndoWrist with seven degrees of freedom, three-dimensional vision, tremor filter, and short learning curve, which prevented injuries from the blood vessels and allowed precise dissection and high flexibility for surgeons [32]. Previous studies proved that one critical barrier to the wide RG application in clinical practice was high costs [12,13,16,17,33,34]. Our study also found that RADG group had higher medical cost than the LADG group.…”
Section: Discussionsupporting
confidence: 56%
“…Although several studies have reported the postoperative complications, the results are still elusive [16,[38][39][40]. A previous study demonstrated that RG showed similar postoperative morbidity to that of LG [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the study by Yang C et al also showed better short-term outcomes with robotic-assisted treatment, again demonstrating the advantages of robotic total gastrectomy in causing a less severe intraoperative inflammatory response and faster recovery of patients after surgery. [36] On the other hand, the high cost of surgery for robot-assisted treatment of gastric cancer is one of its drawbacks. However, there is a paucity of literature comparing the costs of the three surgical procedures, so this outcome indicator has not been included.…”
Section: Total Postoperative Complicationsmentioning
confidence: 99%